Identification of Morphological and Pomological Characteristics of Iraq Pomegranate (Punica granatum L.) Variety Salakhani and Comparing with Variety Zivzik - Khabbat Hasan Al-Jabbari; Mine Pakyürek; Adnan Yaviç (International Journal of Secondary Metabolite)
In this study, morphological and pomological characteristics of Salakhani, local variety of Iraq and Zivzik (Punica granatum L.), local variety of Siirt, were compared. Salakhani variety, which is one of the well-known pomegranate cultivars in Halabja region, has been cultivated for centuries in this region, North of Iraq. Zivzik variety is considered to be one of the important local varieties in Siirt province in the South East of Turkey. Salakhani variety was collected from their natural area in Halabja and Zivzik variety was collected from Zivzik Village in Şirvan. This is the first study comparing both varieties in point of pomological and morphological features. Our study has shown that two varieties are similiar on account of some features on the other hand are also different with regard to some properties. In addition to that the study showed Salakhani has more bigger fruit size and with soft seed than Zivzik pomegranate; conversely, Zivzik cv. has also very juicy fruit and high quality of fruit juice compare with Salakhani. This study has shown the superior characteristics of these two varieties can be the subject of different breeding studies in developing new pomegranate varieties.